Recombinant, rice-produced yeast phytase shows the ability to hydrolyze phytate derived from seed-based feed, and extreme stability during ensilage treatment - Hamada, A.(Mitsui Chemicals Inc., Mobara, Chiba (Japan)); Yamaguchi, K; Harada, M; Horiguchi, K; Takahashi, T; Honda, H (Bioscience, biotechnology, and biochemistry, 2006)
When fresh rice leaves producing yeast Schwanniomyces occidentalis phytase were grounded and mixed with the whole extract of seed-based feed for pigs, the release of orthophosphate increased significantly. More specifically, phytate, a major source of phosphorus in the seeds, was hydrolyzed by heterologous phytase. Moreover, when transgenic rice plants were ensiled for up to 12 weeks, no decrease in the phytase activity of the heterologous enzyme was observed. This result strongly suggests that transgenic rice plants producing yeast phytase can be stored as silage without any loss of enzyme activity until usage as a feed additive.